WISE-2005: Supine treadmill exercise within lower body negative pressure and flywheel resistive exercise as a countermeasure to bed rest-induced bone loss in women during 60-day simulated microgravity - Smith, Scott M.; Zwart, Sara R.; Heer, Martina; Lee, Stuart M.C.; Baecker, Natalie; Meuche, Sabine; Macias, Brandon R.; Shackelford, Linda C.; Schneider, Suzanne; Hargens, Alan R. (Bone (New York, N.Y.), 2008)
Bone loss associated with disuse during bed rest (BR), an analog of space flight, can be attenuated by exercise. In previous studies, the efficacy of either aerobic or resistive exercise countermeasures has been examined separately. We hypothesized that a regimen of combined resistive and aerobic exercise during BR would prevent bone resorption and promote bone formation. After a 20-day ambulatory adaptation to controlled confinement and diet, 16 women participated in a 60-day, 6° head-down-tilt BR and were assigned randomly to one of the two groups. Control subjects (CON, n = 8) performed no countermeasure. Exercise subjects (EX, n = 8) participated in an exercise program during BR, alternating between supine treadmill exercise within lower body negative pressure (3–4 d wk − 1 ) and flywheel resistive exercise (2–3 d wk − 1 ). By the last week of BR, excretion of helical peptide (CON, 79% ± 44 increase; EX, 64% ± 50, mean ± SD) and N-terminal cross-linking telopeptide (CON, 51% ± 34; EX, 43% ± 56), markers of bone resorption, were greater than they were before BR in both groups ( P < 0.05). However, serum concentrations of the bone formation marker procollagen type I N propeptide were greater in EX than CON throughout and after bed rest ( P < 0.05), while concentrations of the bone formation marker bone alkaline phosphatase tended to be greater in EX than CON. Dual-energy X-ray absorptiometry results indicated that the exercise treatment significantly ( P < 0.05) attenuated loss of hip and leg bone mineral density in EX compared to CON. The combination of resistive and aerobic exercise did not prevent bone resorption but did promote bone formation, and helped mitigate the net bone loss associated with simulated microgravity.